Credit and usury in Jewish society in the Mishnah and Talmud - Rozenfeld, Ben Tsiyon 1948- (Boston BRILL, 2023)
Credit is the oxygen of every economy. This volume analyzes ancient rabbinic rulings on credit and usury exposing their underlying economic conceptualization. This was compared to the Roman and Sasanid Worlds and was divided to transactions involving money or products.
Description based on publisher supplied metadata and other sources